Women's Rights in Turkey and the European Union Accession Process: German Media Perspectives. (1st October 2016) - Glüpker-Kesebir, Gitta
ABSTRACT: The German public debate on Turkey's European Union (EU) membership revolves considerably around questions of cultural differences. One way to better understand the dynamics of this debate is to analyze German media coverage of women's rights in Turkey, a contentious issue in this debate. This article investigates how four German newspapers and magazines portray women's rights in Turkey. Contrary to earlier studies that point at biases and stereotypes in German media portrayals of Turkish women living in Germany and of Turks in general, this study finds that the media reflect the diversity of the women's rights issue, by the headscarf topic and problems of women in their families. Instead, they also cover the position of women in the wider public and the legal reforms that have taken place in Turkey since the late 1990s. Although progress is the most frequent tendency indicated in the press reports, the women's rights developments are only linked in a quarter of all reports to the EU accession process.